Folliculotropic T‐cell infiltrates associated with B‐cell chronic lymphocytic leukaemia or MALT lymphoma may reveal either true mycosis fungoides or pseudolymphomatous reaction: seven cases and review of the literature. (19th March 2014) - Ingen‐Housz‐Oro, S.; Franck, N.; Beneton, N.; Fauconneau, A.; Do‐Pham, G.; Carlotti, A.; Petit, T.; Liolios, I.; Bara, C.; Carpentier, H.; Storelli, D.; Prophette, B.; et al.
Abstract Background Mycosis fungoides (MF) and pseudo‐MF (or MF simulant) can be associated with B‐cell malignancies, but distinction between a true neoplasm and a reactive process may be difficult. Objectives To report seven patients with B‐cell malignancy and folliculotropic MF or pseudo‐MF and emphasize on criteria allowing distinction between the two conditions. Methods We retrospectively and prospectively included seven patients with B‐cell malignancy who presented skin lesions histologically consisting in a folliculotropic T‐cell infiltrate and reviewed the literature on the topic. Results Four men and three women had a chronic lymphocytic leukaemia (n = 6) or a MALT‐type lymphoma (n = 1). Five patients had localized papules, and two had patches and plaques. Histological examination showed in all cases a diffuse dermal T‐cell infiltrate with folliculotropic involvement and follicular mucinosis associated with clusters of the B‐cell lymphoma, without significant expression of follicular helper T‐cell markers. T‐cell rearrangement studies showed a polyclonal pattern in the patients with papules and a monoclonal pattern in the cases of patches and plaques. Papular lesions had an indolent evolution, whereas patches and plaques persisted or worsened into transformed MF. Conclusion Folliculotropic T‐cell infiltrates associated with B‐cell malignancies can be either a true folliculotropic MF or a pseudo‐MF. The distinction between both conditions cannot rely only on the histopathological aspect, but needs both a clinical pathological correlation and the search for a dominant T‐cell clone. Whether the neoplastic T and B cells derive from a common ancestor or the T‐cell proliferation is promoted by the underlying B‐cell lymphoma remains unsolved, but interaction between B and T cell in the skin does not appear to be dependent on a TFH differentiation of the T‐cell infiltrate.